Analisis Struktur, Perilaku, Dan Kinerja Pemasaran Susu Sapi Perah Di Desa Manggihan Kecamatan Getasan - Nadindra Martalitha Haryani; Dewi Hastuti; Hendri Wibowo; Endah Subekti (CV. ITTC INDONESIA, 2026)
The marketing of dairy cow milk plays a crucial role in determining distribution efficiency, price formation, and farmers' income. This study aims to analyze the structure, conduct, and performance of dairy milk marketing in Manggihan Village, Getasan District, Semarang Regency, using the Structure-Conduct-Performance (SCP) approach. A quantitative approach with a descriptive method was employed. The cattle population in the village totals 965 head. The sample consisted of 25 farmers selected via random sampling, while marketing institutions were identified using snowball sampling. Data were collected through observation, questionnaire-based interviews, and documentation, utilizing both primary and secondary sources. Data analysis covered market structure (via market share, Concentration Ratio [CR1], and Minimum Efficiency Scale [MES]), market conduct, and market performance (using marketing margins, farmer's share, and marketing efficiency). The results indicate a market structure tending toward monopsony, characterized by a 100% market share for collectors, sales shares of 97.76% to cooperatives and 2.43% to traders, a CR1 of 100%, and an MES of 100%, indicating high barriers to market entry. Three marketing channels were identified, with marketing margins of Rp33,000/liter, Rp3,200/liter, and Rp3,000/liter; farmer's shares of 17.5%, 53.8%, and 70%; and marketing efficiency values ​​of 7.82%, 9.49%, and 4.89%. Channel III was the most efficient, exhibiting the lowest efficiency value and the highest farmer's share. Thus, dairy milk marketing in Manggihan Village remains dominated by a single major buyer, and Channel III offers the most efficient marketing performance.